Strategi Trend Fashion, Promosi Online dan Brand Image Terhadap Minat Beli Fashion Thrifting (Studi Kasus pada Akun Instagram Bassecondstuff_) - Enay Sila; Teguh Hadi Saputra; Nurul Hikmah; Pupung Purnamasari (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This research aims to analyze the influence of fashion trends, online promotions, and brand image on interest in buying fashion thrifting among followers of the Bassecondstuff_ Instagram account. We ran a case study using data from the Bassecondstuff_ Instagram account as a research sample. The results of this research reveal that the fashion trends followed by the account have a significant impact on the buying interest of its followers. Apart from that, effective online promotion and a strong brand image also play an important role in influencing buying interest in fashion thrifting. There is a positive interaction between these three variables, creating a stronger reason for consumers to choose fashion thrift via the Bassecondstuff_ Instagram account. These findings provide important insights for brand managers and researchers in understanding the factors that influence fashion thrifting purchase intentions in the context of social media.